Systematic Review : What is Reported Regarding the Development of Instruments Which Assess Teaching Quality in Higher Education. - Slade, Susan; Baik, Chi; Bearman, Margaret; Carbone, Angela; Hughes-Warrington, Marnie; Neumann, David L.; Smith, Calvin D. (Australian Learning and Teaching Council (ALTC), 2014)
The changing composition of the education workforce within universities, and increasing demands for universities to report on the improvements in teaching quality have highlighted the need for a robust empirical appraisal of professional development activities in learning and teaching. This collaborative project harnessed quantitative research design and insights from open source product development to produce measures of professional development efficacy that can be self-administered by a range of institutions. Moreover, it developed templates and resources that can be used by senior managers to assess professional development provision in learning and teaching in their institutions, and to report with confidence on the efficacy of professional development provisions in improving teaching quality.